A Phase I Dose‐Escalation Study of Linsitinib (OSI‐906), a Small‐Molecule Dual Insulin‐Like Growth Factor‐1 Receptor/Insulin Receptor Kinase Inhibitor, in Combination with Irinotecan in Patients with Advanced Cancer. (23rd August 2018) - Davis, S. Lindsey; Eckhardt, S. Gail; Diamond, Jennifer R.; Messersmith, Wells A.; Dasari, Arvind; Weekes, Colin D.; Lieu, Christopher H.; Kane, Madeline; Choon Tan, Aik; Pitts, Todd M.; Leong, Stephen
Abstract: Lessons Learned: The maximum tolerated dose of the combination of linsitinib and irinotecan is linsitinib 450 mg daily on days 1–3 every 7 days and irinotecan 125 mg/m 2 days 1 and 8 of a 21‐day cycle. The adverse effects associated with the combination are not significantly increased beyond what is expected of each drug as a single agent. Multiple negative trials of insulin‐like growth factor‐1 receptor inhibitors performed in unselected patient populations led to the early discontinuation of linistinib development and this trial. Earlier integration of assessment of potential predictive biomarkers into clinical trials, as was planned in this study, is vital to the development of targeted therapies in oncology. Background: This phase I dose‐escalation study was designed to evaluate the safety and tolerability of the combination of irinotecan and insulin‐like growth factor‐1 receptor (IGF‐1R) inhibitor linsitinib in patients with advanced cancer refractory to standard therapy. Methods: Dose escalation in three specified dose levels was performed according to a standard 3 + 3 design. Dose levels were as follows: (a) linsitinib 400 mg and irinotecan 100 mg/m 2, (b) linsitinib 450 mg and irinotecan 100 mg/m 2, and (c) linsitinib 450 mg and irinotecan 125 mg/m 2 . Linisitinib was administered once daily on days 1–3, 8–10, and 15–17, and irinotecan on days 1 and 8. Assessment of a candidate predictive biomarker was planned in all patients, with further evaluation in an expansion cohort of advanced colorectal cancer. Results: A total of 17 patients were treated, with 1 patient in both cohort 2 and 3 experiencing dose‐limiting toxicity. Linsitinib 450 mg and irinotecan 125 mg/m 2 was the maximum tolerated dose. Sixteen (94%) patients experienced at least one treatment‐related adverse event. Neutropenia was the only grade >3 toxicity (4%). No significant hyperglycemia or QT interval prolongation was noted. No objective responses were observed; 47% ( n = 8) had stable disease with median duration of 5.25 months. Conclusion: Although the combination was determined safe, the study was halted due to termination of linsitinib development, and biomarker testing was not performed.